Performance and Biochemical Responses in Early-Weaned Piglets Fed Diets with Different Protein and Zinc Levels - Mei, Yang; Zhi-Sheng, Wang; An-Guo, Zhou (Pakistan Journal of Nutrition, 2009)
A 2x2 factorial experiment was used to investigate the interaction between dietary Crude Protein (CP) concentration (23 and17%) and zinc supplementation (100 and 3,000 mg/kg, from zinc oxide) on performance and biochemical responses in 32 crossbred piglets weaned at 21 days of age (4 groups of 8 each, 6.3±0.4 kg live weight). Pigs were offered four diets for 28 days after weaning, i.e., 23% CP +100 mg/kg Zn; 17% CP + 100 mg/kg Zn; 23% CP + 3,000 mg/kg Zn and 17% CP + 3,000 mg/kg Zn. There were no interactions between CP and Zn concentration on performances except for on ADG during 3 and 4 weeks. As CP content increasing, ADG, ADFI and Gain: Feed ratio (G:F) were increased across feeding period (p<0.01), however, the incidence of diarrhea was also increased (p<0.05). Supplemented those diets with pharmacological concentrations of Zn improved ADG (p<0.01), ADFI (p<0.05) and G:F (p<0.01) during first 2 weeks after weaning and decreased the incidence of diarrhea significantly (p<0.01), compared to the low-Zn diets. Dietary treatments also affected some enzymes and urea nitrogen in serum, but interactions were observed on AST and LDH from samples of 14 days only (p<0.05). In conclusion, pharmacological concentrations of Zn supplementation was favourable to ensure benefits of high-CP diets on performance of weanling pigs and this may due to its effect on lowing incidence of diarrhea at high CP concentrations. Pharmacological concentrations of Zn had no negative influence on pig health when period was 2 weeks post-weaning.